Validation of pressure drop assessment using 4D flow MRI‐based turbulence production in various shapes of aortic stenoses. Issue 2 (25th September 2018) - Ha, H; Kvitting, JP; Dyverfeldt, P; Ebbers, T
Abstract : Purpose: To validate pressure drop measurements using 4D flow MRI‐based turbulence production in various shapes of stenotic stenoses. Methods: In vitro flow phantoms with seven different 3D‐printed aortic valve geometries were constructed and scanned with 4D flow MRI with six‐directional flow encoding (ICOSA6). The pressure drop through the valve was non‐invasively predicted based on the simplified Bernoulli, the extended Bernoulli, the turbulence production, and the shear‐scaling methods. Linear regression and agreement of the predictions with invasively measured pressure drop were analyzed. Results: All pressure drop predictions using 4D Flow MRI were linearly correlated to the true pressure drop but resulted in different regression slopes. The regression slope and 95% limits of agreement for the simplified Bernoulli method were 1.35 and 11.99 ± 21.72 mm Hg. The regression slope and 95% limits of agreement for the extended Bernoulli method were 1.02 and 0.74 ± 8.48 mm Hg. The regression slope and 95% limits of agreement for the turbulence production method were 0.89 and 0.96 ± 8.01 mm Hg. The shear‐scaling method presented good correlation with an invasively measured pressure drop, but the regression slope varied between 0.36 and 1.00 depending on the shear‐scaling coefficient. Conclusion: The pressure drop assessment based on the turbulence production method agrees well with the extended Bernoulli method and invasively measured pressure drop in various shapes of the aortic valve. Turbulence‐based pressure drop estimation can, as a complement to the conventional Bernoulli method, play a role in the assessment of valve diseases.